Umbilical polyp, Meckel's diverticulum, and incomplete type-1 ileal atresia: A case report - Mumtaz Ahmed Qureshi; Sana Muhammed Aslam; Imtiaz Ahmed Qureshi (Elsevier, 2024)
Introduction: Meckel's diverticulum (MD) is a diverticulum that develops due to the incomplete obliteration of the omphalomesenteric duct, which connects the developing embryo to the yolk sac. We present a case involving the unusual coexistence of a Meckel's diverticulum, an umbilical polyp, and an incomplete type-1 ileal atresia. Case report: A 20-day-old full-term female presented with a small umbilical polyp associated with a mucous and bloody discharge. There was no history of stool or urine draining through the umbilical lesion. An abdominal ultrasound was done and showed no abnormalities. Blood tests were all normal. We decided to do a laparotomy through a curved infra-umbilical incision. The umbilical polyp was associated with a Meckel's diverticulum (MD). Following the resection of the MD, we found a fenestrated membrane in the lumen of the proximal ileum, consistent with an incomplete type-1 ileal atresia. We resected the segment of the proximal ileum that contained the membrane and did an end-to-end anastomosis. We then reconstructed the umbilicus after resecting the granuloma. The patient had an uneventful recovery. Histological examination revealed a perforated membrane in the ileum and a congenital umbilical polyp with granulation tissue. No ectopic gastric or pancreatic tissue was found in the MD. Conclusion: The association between MD, umbilical polyp, and incomplete type 1-ileal atresia is rare, and its diagnosis before a surgical exploration is challenging. The lumen of the bowel at the base of a MD should be inspected to rule out the presence of a fenestrated membrane.